Relocation and process of territorialisation in the Rural Sustainable City Nuevo Juan del Grijalva - Arévalo-Peña, Martha Liliana (2020)
Due to the flooding of the communal territory Juan de Grijalva in the Municipality of Ostuacan, state of Chiapas, and the risk in the zone, this town and others were relocated to the Rural Sustainable City (CRS by its acronym in Spanish), which is part of a public policy of the federal and state governments during the presidency of Felipe Calderon and the governorship of Juan Sabines (2006-2012). The CRS was posed as a regional development strategy to address population dispersion and to eradicate poverty in an effective way. In this context, the objective of this work is to analyze what has happened with the residents relocated during the period of 2011-2016, evidencing their processes of territorialisation. This research was developed by using qualitative research methods, particularly the ethnographic method, supported by participant observations, fields notes and interviews. A comparative method was also employed, which allowed for the observation of the processes of territorialisation of the residents of the CRS over a period of 5 years. The results point out that the federal and state governments lack knowledge about their territory and population. They also highlight the absence of monitoring of public policies that are executed and the null participation of the population in them, a situation that perpetuates poverty instead of eradicating it.